The Financial Aspects of Islamic Education (An Idea to Improve the Quality of Islamic Education in Islamic Boarding Schools) - Mukti, Abd; Budianti, Yusnaili; Hamdani, Hamdani (Universitas Malikussaleh, 2020)
Funding for education in Islam basically focuses on distributing education costs and burdens that must be borne by the community. Things that need to be considered in education financing are the amount of money that must be spent and where the source of the money is obtained. Thus, based on the source, the cost of education is obtained from the cost of education that comes from the government, the community, and the Baitul Mal. The main obstacle in financing Islamic education is due to limited sources of funds, low support for the community. In this case the thought about the source of education costs, at least the education providers must have planned it in detail because if the implementation process only depends on certain parties, in this case, the education providers are not serious in developing it. All these aspects are the concern of Pesantren in providing education to students, thus the educational aspect becomes part of the aspect of assessment that is very important in learning. The right attitude to respond to today's developments is expressed by the values of moral education developed through management functions to improve the quality of Islamic education in Islamic boarding schools. By implementing it in formal education, Pesantren education, informal education, and non-formal education, it will produce spiritual values, ethical honesty values, and tolerance values. Based on this view, the program implemented felt by all Pesantren residents through a good financial system.